(untitled) (Health Renaissance, 2017)
This is a case report of a three years old male child presented in the Otolaryngology and Head & Neck Surgery with chief complain of bleeding from the left nostril since seven days with nasal itching which was later diagnosed to be living foreign body leech causing epistaxis. Health Renaissance 2015;13(2): 178-179